MEMS and nanotechnology. Volume 2 proceedings of the 2010 annual conference on experimental and applied mechanics - International Symposium on MEMS and Nanotechnology 2010 Indianapolis, Ind.); Proulx, Tom (Thomas William).; SpringerLink (Online service). (New York Springer, 2011)
The 11th International Symposium on MEMS and Nanotechnology is the second volume of six from the Annual Conference of the Society for Experimental Mechanics 2010. It brings together 40 chapters on Microelectromechanical Systems and Nanotechnology. It presents early findings from experimental and computational investigations on MEMS and Nanotechnology including contributions on Nanomechanical Standards, Magneto-mechanical MEMS Sensors, Piezoelectric MEMS for Energy Harvesting, and Linear and Nonlinear Mass Sensing.
Electronic reproduction.
Keywords: Microelectromechanical systems -- Congresses; Nanotechnology -- Congresses; Electronic books